2015
DOI: 10.1002/etc.2952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the capacity of two biotic ligand models to predict chronic copper toxicity to two Daphnia magna clones and formulation of a generalized bioavailability model

Abstract: Although it is increasingly recognized that biotic ligand models (BLMs) are valuable in the risk assessment of metals in aquatic systems, the use of 2 differently structured and parameterized BLMs (1 in the United States and another in the European Union) to obtain bioavailability-based chronic water quality criteria for copper is worthy of further investigation. In the present study, the authors evaluated the predictive capacity of these 2 BLMs for a large dataset of chronic copper toxicity data with 2 Daphni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 31 publications
(85 reference statements)
0
29
0
Order By: Relevance
“…The gBAM was developed as described in Van Regenmortel et al . The first type of model (gBAM‐A) only incorporates a pH constant and is structurally similar to bioavailability models developed with algae for Zn , Cu , and Ni and recently with D. magna for Cu (Equation ). log10true(EC50Zn2+true)=normalQ50normalSpH×pH …”
Section: Resultsmentioning
confidence: 99%
“…The gBAM was developed as described in Van Regenmortel et al . The first type of model (gBAM‐A) only incorporates a pH constant and is structurally similar to bioavailability models developed with algae for Zn , Cu , and Ni and recently with D. magna for Cu (Equation ). log10true(EC50Zn2+true)=normalQ50normalSpH×pH …”
Section: Resultsmentioning
confidence: 99%
“…The effect of temperature on chronic Ni toxicity significantly differed among clones. A previous study demonstrated an effect of pH on the chronic toxicity of Cu between 2 clones . Therefore, the study of multiple clones is necessary to investigate the effect of environmental variables on chronic metal toxicity to D. magna .…”
Section: Discussionmentioning
confidence: 99%
“…Both existing fish BLMs formulate the effect of pH on free Cu 2+ ion toxicity as a linear single‐site competition effect of H + at the Cu 2+ uptake site (i.e., the biotic ligands). An alternative formulation of the pH effect in the chronic Cu Daphnia bioavailability model has recently been proposed through the use of gBAMs (Van Regenmortel et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The gBAMs are an alternative to the existing BLMs to predict chronic effect concentrations for Cu (and other metals) in freshwater organisms (Mebane et al 2020), such as fish (e.g., nickel [Ni]; Deleebeeck et al 2007), D. magna (e.g., for Cu and zinc [Zn]; Van Regenmortel et al 2015, 2017), and algae (e.g., for Cu; De Schamphelaere and Janssen 2006). The chronic Cu Daphnia gBAM combines a log‐linear pH effect on free Cu 2+ ion toxicity with conventional linear protective effects of major cations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation